2015
DOI: 10.1111/jre.12294
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a signaling induces murine dental follicle cells to differentiate into cementoblastic/osteoblastic cells via an osterix‐dependent pathway

Abstract: These findings suggest that HERS has a potential role in stimulating cementoblast/osteoblast differentiation of dental follicle cells via the Wnt/β-catenin signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 50 publications
(70 reference statements)
1
48
0
Order By: Relevance
“…It was noted that treatment with siWnt5a as well as the addition of rWnt5a had no significant effect on the proliferative response compared with that in the respective control (data not shown), indicating that the inhibitory effects of rWnt5a were not a reflection of alterations in the cell number. On the other hand, the expression of the Osx gene, which was reported to be upregulated by Wnt3a [18], was not significantly affected by the addition of 100 ng/ml rWnt5a (Fig. 3D).…”
Section: Wnt5a Signaling Is a Negative Regulator For Canonical Wntmedmentioning
confidence: 80%
See 3 more Smart Citations
“…It was noted that treatment with siWnt5a as well as the addition of rWnt5a had no significant effect on the proliferative response compared with that in the respective control (data not shown), indicating that the inhibitory effects of rWnt5a were not a reflection of alterations in the cell number. On the other hand, the expression of the Osx gene, which was reported to be upregulated by Wnt3a [18], was not significantly affected by the addition of 100 ng/ml rWnt5a (Fig. 3D).…”
Section: Wnt5a Signaling Is a Negative Regulator For Canonical Wntmedmentioning
confidence: 80%
“…dental follicle cells, regarded as precursor cells of cementoblasts [17]. Furthermore, we have recently reported that the expression of Wnt3a was detected on HERS [18], which is considered to have an inductive role in initiating root formation by epithelial-mesenchymal interaction. On the other hand, we have reported the opposite effect of Wnt3a for highly differentiated cementoblasts by showing that canonical Wnt/β-catenin signaling stimulated by rWnt3a inhibits the cementoblastic differentiation of murine immortalized cementoblasts, OCCM30, with reduced gene expression levels of ALP, Runx2, and Osx [19].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In immortalized murine dental follicle cells, Wnt3a induced ALP expression. Moreover, Wnt3a induced Runx2 and Osterix in these cells, suggesting a potential role of HERS in stimulating cementoblast/osteoblast differentiation of dental follicle cells via the canonical Wnt signaling pathway [63]. The activation of the canonical Wnt signaling has recently been reported to induce in vivo cementum regeneration in the rat periodontal defect model and in vitro cementoblast differentiation of human periodontal ligament cells [64].…”
Section: Canonical Wnt Signaling Pathway Components In the Tooth And mentioning
confidence: 96%